Diversity and distribution of North Atlantic Lepechinellidae (Amphipoda: Crustacea). Issue 4 (25th April 2020) - Lörz, Anne-Nina; Brix, Saskia; Jażdżewska, Anna M; Hughes, Lauren Elizabeth
Abstract: North Atlantic lepechinellid amphipod species were investigated using morphological and molecular techniques based on material collected during two IceAGE expeditions in 2011 and 2013 (Ice landic marine A nimals: G enetics and E cology). The presence of eyes is reported for the first time for the family Lepechinellidae. Four lepechinellid species, Lepechinella grimi, L. helgii, L. skarphedini and Lepechinelloides karii were distinct across morphological, COI and 16S data. Lepechinella arctica, L. norvegica and L. victoriae were seen to be morphologically similar. No morphological or molecular separation was observed between L. arctica and L. norvegica, indicating that these taxa should not be considered separate species. Full illustrations of habitus and mouthparts are presented for L. arctica and a new synonymy is provided recognizing L. norvegica as a junior synonym of L. arctica . While L. victoriae shows little morphological variation from L. arctica, COI and 16S data show this taxon as genetically distinct. Furthermore, new geographic and depth ranges for North Atlantic and Arctic lephechinellids are provided.